2009
DOI: 10.4161/cc.8.19.9636
|View full text |Cite
|
Sign up to set email alerts
|

The apoptosis modulating role of SAP (SLAM associated protein) contributes to the symptomatology of the X linked lymphoproliferative disease

Abstract: The involvement of SAP in the apoptotic machinery provides a further aspect in the complex syndrome of XLP. Functional impairment of SAP leads to defective apoptotic responses. Activation induced apoptosis plays a pivotal role in the termination of the lymphocyte proliferation in IM. This mechanism is inefficient in XLP patients. In addition, in the absence of SAP, lymphoma development may be promoted by the illegitimate survival of lymphocytes with damaged DNA that would be normally eliminated by apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Evidence from previous studies suggested that SAP deficiency could lead to the inhibition of NK cytotoxicity in humans [28], [55][56]. It has also been shown that in the absence of SAP, lymphoma development would normally be eliminated by apoptosis in patients with X-linked lymphoproliferative disease [57]. However, the analysis of potential apoptosis caused by reducing expression of SAP indicated that the deficiency of SAP would not lead to the significant apoptosis of NK92 cells (Data not show).…”
Section: Discussionmentioning
confidence: 77%
“…Evidence from previous studies suggested that SAP deficiency could lead to the inhibition of NK cytotoxicity in humans [28], [55][56]. It has also been shown that in the absence of SAP, lymphoma development would normally be eliminated by apoptosis in patients with X-linked lymphoproliferative disease [57]. However, the analysis of potential apoptosis caused by reducing expression of SAP indicated that the deficiency of SAP would not lead to the significant apoptosis of NK92 cells (Data not show).…”
Section: Discussionmentioning
confidence: 77%
“…Higher levels of SAP can interact with Valosin-containing protein (VCP/p97) and may interfere with NFκB signaling. 5,22 To test the involvement of p53 in regulating SAP levels in activated T cells, we used Nutlin-3 to specifically induce p53 accumulation and p53 transcription activity. Nutlin-3 treatment of non-activated T cells for 6 h resulted in upregulation of SAP mRNA along with other known p53-responsive genes, i.e., p21 and Bax, 23 which is consistent with SAP being a transcription target of p53.…”
Section: Separation Activation and Treatment Of Primary T Cellmentioning
confidence: 99%
“…Pathogenic NLRC4 variants render constitutive NLRC4 inflammasome activation driving high levels of IL-1β and most importantly IL-18 that results in macrophage activation/HLH phenotype [22,23]. Patients with X-linked lymphoproliferative syndromes (SH2DIA, BIRC4 and XIAP) characteristically associated with increased susceptibility to infection with Epstein Barr virus, dysgammaglobulinemia and lymphoma can also develop life-threatening HLH [24,25]. Among immune dysregulation group, syndromes with autoimmunity or immune dysregulation with colitis are included.…”
Section: Diseases Of Immune Dysregulationmentioning
confidence: 99%